Regulatory T cells in peripheral tissue tolerance and diseases - Cheru, Nardos; Hafler, David A.; Sumida, Tomokazu S. (Frontiers in Immunology, 2023)
Maintenance of peripheral tolerance by CD4+Foxp3+ regulatory T cells (Tregs) is essential for regulating autoreactive T cells. The loss of function of Foxp3 leads to autoimmune disease in both animals and humans. An example is the rare, X-linked recessive disorder known as IPEX (Immune Dysregulation, Polyendocrinopathy, Enteropathy X-linked) syndrome. In more common human autoimmune diseases, defects in Treg function are accompanied with aberrant effector cytokines such as IFNγ. It has recently become appreciated that Tregs plays an important role in not only maintaining immune homeostasis but also in establishing the tissue microenvironment and homeostasis of non-lymphoid tissues. Tissue resident Tregs show profiles that are unique to their local environments which are composed of both immune and non-immune cells. Core tissue-residence gene signatures are shared across different tissue Tregs and are crucial to homeostatic regulation and maintaining the tissue Treg pool in a steady state. Through interaction with immunocytes and non-immunocytes, tissue Tregs exert a suppressive function via conventional ways involving contact dependent and independent processes. In addition, tissue resident Tregs communicate with other tissue resident cells which allows Tregs to adopt to their local microenvironment. These bidirectional interactions are dependent on the specific tissue environment. Here, we summarize the recent advancements of tissue Treg studies in both human and mice, and discuss the molecular mechanisms that maintain tissue homeostasis and prevent pathogenesis.